Formulasi Dan Uji Aktivitas Antioksidan Sediaan Facemist Ekstrak Umbi Wortel (Daucus Carota L) - Alin Marlina; Gina Septiani Agustien; Susanti Susanti (Jurnal Mahasiswa Ilmu Kesehatan, 2023)
Excessive exposure to sunlight is a source of free radicals that cause damage to the skin such as redness, dullness, and aging, so skincare containing antioxidants is needed, one of which is a face mist made from carrot root extract. The carrot (Daucus carota L) is a plant rich in antioxidants such as β-carotene and vitamin C which can counteract free radicals. This research aims to determine whether carrot tuber extract can be formulated in a face mist preparation and to determine the value of antioxidant activity in the carrot tuber extract face mist preparation. The method used in this study is the experimental method. Preparation of carrot root extract was carried out using the maceration method with 70% ethanol solvent. Facemist carrot root extracts was made with various concentrations of FI 1%, FII 3%, and FIII 5%. All preparations were subjected to physical stability (organoleptic, pH, spray spreadability, dry time, and homogeneity) and antioxidant activity tests using the DPPH method. The results of physical stability stated that all formulas met the physical quality requirements. The antioxidant activity value of carrot tuber extracts facemist at concentrations of 1%, 3%, and 5% has an IC₅₀ value of 41.31ppm, 34.64ppm, and 28.80ppm respectively. This value is in the very strong category. The conclusion of this study is that carrot root extract can be formulated as a face mist preparation and has a very strong antioxidant value.